Ethical problems in nursing management - a cross-sectional survey about solving problems - Elina Aitamaa; Riitta Suhonen; Pauli Puukka; Helena Leino-Kilpi (BMC, 2019)
Abstract Background Nurse managers encounter a wide range of ethical problems related to patients, staff, the organisation and themselves. However, little is known about the methods they use to try to solve these problems. In this study, our goal is to fill this knowledge gap by investigating the ethical problems encountered by nurse managers, the frequency of use and usefulness of different methods to solve these problems, and the background factors associated with the use of the methods. Methods A cross-sectional survey study was conducted in November 2014-May 2015 in Finland. The data were collected from nurse managers in strategic, middle and ward management (n = 214) using a questionnaire developed for this study. The questionnaire consisted of four parts: socio-demographic background factors, frequency and difficulty of ethical problems in nursing management, frequency of use and usefulness of the methods in solving ethical problems, and work-related background factors. Results Discussions with nurses was the most frequently used method, used by 94% of the nurse managers either often or always in the case of ethical problems, followed by the use of personal values (74%) and discussions with manager colleagues (70%). However, almost all methods in the different groups - discussion and deliberation, use of outside experts, written instructions and ethical principles, acts and degrees as well as work arrangements - were considered somewhat or very useful by more than half of the respondents. The use of outside experts was the least used and the least useful method. Conclusions When solving ethical problems, nurse managers use most frequently the same methods as a few decades ago. A more diverse range of methods would be helpful in ethical problem-solving. The use of outside experts, ethics literature and codes of ethics should be combined with ethical reasoning and decision-making to get new dimensions and outside knowledge.